Pengaruh Boikot Produk Unilever Dan Lapangan Kerja Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun (2014-2023) - Zahara Aulia; Bagas Bimantoro; Arif Dwi Wibowo; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In this research, we will discuss the boycott of Unilever products and employment on economic growth. The boycott of Uniliver products and employment are closely related, where if Unilever product revenues in Indonesia experience a decline, which makes the Unilever company reduce production, this can cause employee layoffs and create jobs. employment decreases, if employment decreases there will be a lot of unemployment which can affect economic growth. The results of the research are that Unilever products have an insignificant negative effect on economic growth, and employment has an insignificant negative effect on economic growth.